Ultrasonography in Assessment of Cervical Lymph Nodes - Sabba Sachi Sarkar (Asian Journal of Medical Radiological Research, 2020)
Background: Cervical lymphadenopathy is one of the most common causes of mass in head and neck region there are various causes of CL common among them are reactive, tuberculosis, metastasis and lymphoma. The present study assessed cervical lymph nodes using Ultrasonography (USG). Subjects and Methods: The present study was conducted on 78 patients who underwent USG of neck of both genders. The cervical lymph nodes classified based on the location in the neck into VII levels according to AJCC classification. Results: Age group 11-20 comprised of 8 cases, 21-30 had 15, 31-40 had 20, 41-50 had 27 and 51-60 had 8 cases. USG showed 40 cases malignant, 27 reactive and 11 tubercular.The difference was significant (P< 0.05). Histopathology showed 34 cases malignant, 32 reactive and 10 tubercular. The difference was significant (P< 0.05).FNAC had sensitivity of 98.2% and specificity of 94.4%, USG had sensitivity of 91.2% and specificity of 86.2%. The difference was significant (P< 0.05). Conclusion: Authors found that ultrasonographic examination proved as a valuable primary investigation to identify lymph nodes.